(untitled) (Research, Society and Development, 2020)
The Brazilian cerrado is one of the richest biomes in the world, with native and exotic fruit species, but little explored. Given this diversity, stands out the red jambo, an exotic fruit with remarkable sensory characteristics, but highly perishable, with reduced shelf life. Foam-mat drying (FMD) is a technique that aids in the preservation of fruits, resulting in a powder product with desirable characteristics such as high porosity and rehydration capacity. In this sense, this work aimed to analyze the influence of drying temperature, besides evaluating the kinetics and mathematical modeling of experimental data. In addition, the physicochemical properties of fresh jambo pulp were determined and after the foam layer drying process. Drying was performed in an air circulation oven at 50, 60, 70ºC, using a concentration of 4.5% (w/w) emulsifier. The Lewis, Midilli and Kucuk and Page mathematical models were adjusted to the experimental data, being the best fit obtained using the Midilli and Kucuk and Page models. The fruit powders presented acidic pH (throne of 3.5), the vitamin C content decreased as the temperature increased (108.16; 88.58 and 62,16 mg at 50, 60 and 70ºC , respectively) and ash content increased significantly in dry powder samples due to the addition of foaming agents.